Anaerobic reduction of 2, 6‐dinitrotoluene by Shewanella oneidensis MR‐1: Roles of Mtr respiratory pathway and NfnB. Issue 4 (21st November 2016) - Liu, Dong‐Feng; Min, Di; Cheng, Lei; Zhang, Feng; Li, Dao‐Bo; Xiao, Xiang; Sheng, Guo‐Ping; Yu, Han‐Qing
ABSTRACT: Dinitrotoluene (DNT) is a widely present pollutant in aquatic environments, and its biodegradation is an economically attractive way to effectively removal. In aquatic environments, the presence of electrochemically active bacteria (EAB) could contribute to the anaerobic bioreduction of DNT. However, the mechanism behind such a biodegradation process at gene level remains to be further elucidated. In this work, the anaerobic reduction of 2, 6‐dinitrotoluene (2, 6‐DNT) by Shewanella oneidensis MR‐1, a typical EAB in aquatic environments, was investigated. S. oneidensis MR‐1 was found to be able to obtain energy for growth through the anaerobic respiration on 2, 6‐DNT. Experimental results show that the Mtr respiratory pathway, a transmembrane electron transport chain, was involved in the 2, 6‐DNT bioreduction. Knockout of cym A or nfn B resulted in a substantial loss of its 2, 6‐DNT‐reducing ability, indicating that both CymA and NfnB were the key proteins in the microbial electron transfer chain. The genetic analysis further confirms that the Mtr respiratory pathway and NfnB are mainly responsible for the anaerobic reduction of 2, 6‐DNT by S. oneidensis MR‐1. This work is useful to better understand the anaerobic bioreduction of nitroaromatic compounds in aquatic environments and remediate the environments contaminated by nitroaromatic compounds. Biotechnol. Bioeng. 2017;114: 761–768. © 2016 Wiley Periodicals, Inc. Abstract : The anaerobic reduction mechanism of 2, 6‐dinitrotoluene (2, 6‐DNT) by Shewanella oneidensis MR‐1, a typical EAB, was investigated. Liu and coworkers have found that S. oneidensis MR‐1 was able to obtain energy for growth through the anaerobic respiration on 2, 6‐DNT. Both intracellular and extracellular reductions contributed to such a rapid bioreduction.